REFORMASI SUMBER DAYA MANUSIA APARATUR NEGARA - Sofian Effendi (Jurnal Manajemen Kepegawaian, 2010)
The bureaucratic reform agenda during the first year will be expanded to 8 in 2009, a term of SBY presidency has only given priority to limited number of departments and agencies, 1 in 2008, expanded to 3 and cover three areas; administrative efficiency, administrative structures and human resource management. As an incentive to further reform, the government through the Ministry of Finance is rewarding agencies which can demonstrate performance improvements with an additional performance budget, given to staff as performance bonuses. These reform initiatives are seen as the first of a three phase approach to bureaucratic reform with the second phase the 2010-14 presidential term and the last phase being completed by 2020-2024. The second phase of Indonesia’s bureaucratic reform needs to go beyond the three areas and the limited approach. To build a professional, a-political and high performance Indonesia’s civil service the reform initiatives should focus on the following areas: a) Develop position based human resource management system, b) Creating an independent authority for Indonesia’s civil service, c) Develop multi-category civil service, d) Launch salary and pension reforms. Key words: reform, human resources, professional